Romanian households’ income inequality - Maria MOLNAR (Revista Română de Statistică, 2010)
This paper presents the results of the measurement of Romanianhouseholds’ income inequality during 1995-2008 years. The measurementis based on a set of inequality indicators, estimated by using data collected by household budget surveys. The estimates of all indicators applied in the evaluation show an increase in inequality from 2000 year to 2006, followed by a clear decrease during 2007 and 2008. The estimates for 1995 and 2000 didn’t reveal an unambiguous tendency: some of them indicate an increase, while others suggest a decrease of income inequality. The paper is a first outcome of a research project on social inequality and polarization.